Active phytoconstituents to tackle the resistance mechanism of MDR and XDR bacteria: A critical review - Subhasmita Mallik; Jatindra Mohanty; Subham Jyoti Sahoo (Microbes and Infectious Diseases)
Background: The extensive use of antibiotics and the rapid emergence of multiple drug resistance bacteria (MDR) and extensively drug resistant (XDR) are significant global public health issues. Recent findings suggest multiple approaches to tackling these problems, including developing alternative compounds with antimicrobial activities, managing existing antimicrobials, nanotechnology-based drug, genome editing and rapidly detecting AMR pathogens etc. New antibiotics targeting priority superbugs are entering the market or are in clinical development. Continuous identification of effective treatment strategies is crucial due to the potential for resistance development against new antibiotics. Among these strategies, employing alternative compounds such as phytochemicals, either alone or in combination with other antibacterial agents appears to be both effective and safe for combating them. Our aim in this review is to investigate the efficacy of phytochemicals in combating multi-drug resistant (MDR) and extensively drug resistant (XDR) bacteria by analysing their bioactive components, and their impact on various resistance mechanisms.